The Effects of Transformational Leadership and Mediating Factors on the Organizational Success Using Structural Equation Modeling: A Case Study. Issue 1 (January 2016) - Ravangard, Ramin; Karimi, Sakine; Farhadi, Payam; Sajjadnia, Zahra; Shokrpour, Nasrin
Abstract : This study was undertaken to determine the effects of transformational leadership (TL) and mediating factors on organizational success (OS) from the administrative, financial, and support employees' perspective in teaching hospitals affiliated with Shiraz University of Medical Sciences using structural equation modeling. Three hundred administrative and financial employees were selected, using stratified sampling proportional to size and simple random sampling. Data were collected using 5 questionnaires and analyzed using SPSS 21.0 and Lisrel 8.5 through Pearson correlation coefficient and path analysis and confirmatory factor analysis methods. Results showed that TL had significant positive effects on the 3 mediating factors, including organizational culture ( t = 15.31), organizational citizenship behavior (OCB) ( t = 10.06), and social capital ( t = 10.25). Also, the organizational culture ( t = 2.26), OCB ( t = 3.48), and social capital ( t = 7.41) had significant positive effects on OS. According to the results, TL had an indirect effect on OS. Therefore, organizations can achieve more success by strengthening organizational culture, OCB, and social capital through using transformational leadership style. Therefore, in order to increase OS, the following recommendations are made: supporting and encouraging new ideas in the organization, promoting teamwork, strengthening intergroup and intragroup relationships, planning to strengthen and enrich the social and organizational culture, considering the promotion of social capital in the employee training, establishing a system to give rewards to the employees performing extra-role activities, providing a suitable environment for creative employees, and so on.